The use of DEA (Data Envelopment Analysis) methodology to evaluate the impact of ICT on productivity in the hotel sector - Cidália Leal Paço; Juan Manuel Cepeda Pérez (Via@)
The main aim of this paper is to analyse the nonparametric technique used in many studies of the hospitality sector. The econometric frontier approach – DEA (Data Envelopment Analysis) – allows the use of multiple inputs/outputs without imposing any functional form on data or making assumptions of inefficiency. Technical Efficiency refers to the ability of a hotel to get the maximum output for a given set of inputs, with reference to a production function. Conversely, Allocative Efficiency concerns the ability of a hotel to use the inputs and produce outputs in optimal proportions given their prices. These two measures are combined to provide the measurement of total Economic Efficiency. The DEA model permits the measurement of both when we have information about prices and we want to consider a behavioural objective, such as minimising costs and maximising revenues. In the production-oriented models, DEA proposes the identifying of inefficiency as a proportional increase in production use. An input-oriented model for technical inefficiency with a proportional decrease in the use of the inputs can be used. With regard to hotels, market guidance seems to be the natural choice due to their competitive position.